The distribution of the trace element contents in lignite and ash from Drama lignite deposit, using multivariate statistical analysis - PANILAS, S.; HATZIYANNIS, G. (Bulletin of the Geological Society of Greece, 2001)
Multivariate statistical analysis was used on existing geochemical data of the Drama lignite deposit, eastern Macedonia, Greece. Factor analysis with varimax rotation technique was applied to study the distribution of major, trace and rare earth elements in the lignite and 850°C lignitic ash, to find a small set of factors that could explain most of the geochemical variability. The study showed that major elements AI, Na, Κ, contained in the lignite samples, presented high correlation with most of the trace and rare earth elements. In 850°C lignitic ashes major and trace elements present different redistribution. Only Al remained correlated with the trace elements Co, Cr, Rb, Ta, Th, Ti, Sc and rare earths related with inorganic matter in the lignite beds. Trace elements Fe, Mo, U, V, W, and Lu were associated with organic matter of lignite and had also been affected by the depositional environment.